Parent-Researcher Perspectives on Role Intersectionality Related to Autism Research - Hall, Laura J.; Hoxie, Natalie A.; Grundon, Gretchen S.; Cordero, Yulian N. (Frontiers in Rehabilitation Sciences, 2022)
Although parents of children with autism who are also experts in a related profession have been instrumental in shaping current practices, there is little known about parent-researchers and the benefits and obstacles to including individuals with these intersectional identities on autism focused research teams. The following study used collaborative autoethnographies from three parent-researchers hired for a large scale, federally funded project. The parent-researchers, and co-authors, collaborated on all phases of the reported study. Common themes generated from the shared perspectives included: prioritizing children and professional sacrifices; professional training as an asset for parents; potential bias towards parents in professional contexts; assets as parent-professionals; and obstacles for maintaining intersectional roles of parent-professionals. Recommendations for autism researchers and considerations for employing and supporting parent-researchers are discussed.